Mind Over Matter: Confronting Challenges in Post-Mortem Brain Biobanking for Glioblastoma Multiforme. Issue 16 (April 2021) - Griffin, Cassandra; Vilain, Ricardo; King, Simon; Nixon, Sandy; Gooley, Alisha; Bray, Samara; Lynam, James; Walker, Marjorie M; Scott, Rodney J; Paul, Christine
Over the past 10 years, there has been limited progress for the treatment of brain cancer and outcomes for patients are not much improved. For brain cancer researchers, a major obstacle to biomarker driven research is limited access to brain cancer tissue for research purposes. The Mark Hughes Foundation Brain Biobank is one of the first post-mortem adult brain banks in Australia to operate with protocols specifically developed for brain cancer. Located within the Hunter New England Local Health District and operated by Hunter Cancer Biobank, the boundaries of service provided by the Brain Bank extend well into the surrounding regional and rural areas of the Local Health District and beyond. Brain cancer biobanking is challenging. There are conflicting international guidelines for best practice and unanswered questions relating to scientific, psychosocial and operational practices. To address this challenge, a best practice model was developed, informed by a consensus of existing data but with consideration of the difficulties associated with operating in regional or resource poor settings. The regional application of this model was challenged following the presentation of a donor located in a remote area, 380km away from the biobank. This required biobank staff to overcome numerous obstacles including long distance patient transport, lack of palliative care staff, death in the home and limited rural outreach services. Through the establishment of shared goals, contingency planning and the development of an informal infrastructure, the donation was facilitated within the required timeframe. This experience demonstrates the importance of collaboration and networking to overcome resource insufficiency and geographical challenges in rural cancer research programmes.